Cold-stored cadaveric venous allograft for superior mesenteric/portal vein reconstruction during pancreatic surgery. Issue 7 (July 2016) - Kleive, Dyre; Berstad, Audun E.; Verbeke, Caroline S.; Haugvik, Sven P.; Gladhaug, Ivar P.; Line, Pål-Dag; Labori, Knut J.
Abstract: Background: SMV/PV resection has become common practice in pancreatic surgery. The aim of this study was to evaluate the technical feasibility and surgical outcome of using cold-stored cadaveric venous allografts (AG) for superior mesenteric vein (SMV) and portal vein (PV) reconstruction during pancreatectomy. Methods: Patients who underwent pancreatic resection with concomitant vascular resection and reconstruction with AG between January 2006 and December 2014 were identified from our institutional prospective database. Medical records and pre- and postoperative CT-images were reviewed. Results: Forty-five patients underwent SMV/PV reconstruction with AG interposition (n = 37) or AG patch (n = 8). The median operative time and blood loss were 488 min (IQR: 450–551) and 900 ml (IQR: 600-2000), respectively. Major morbidity (Clavien ≥ III) occurred in 16 patients. Four patients were reoperated (thrombosis n = 2, graft kinking/low flow n = 2) and in-hospital mortality occurred in two patients. On last available CT scan, 3 patients had thrombosis, all of whom also had local recurrence. Estimated cumulative patency rate (reduction in SMV/PV luminal diameter <70% and no thrombosis) at 12 months was 52%. Conclusion: Cold-stored cadaveric venous AG for SMV/PV reconstruction during pancreatic surgery is safe and associated with acceptable long-term patency.